Chief Human Resource Officers and accounting disclosures: illuminating the firm’s most important asset or window dressing? - Michaelides, Andrie; Vafeas, Nikos (Elsevier, 2023)
Social activism, including movements towards equal pay, gender rights, and racial equality, has heightened public scrutiny, exerting pressure on firms to reassess and reform their human resource practices to ensure they align with current social and ethical norms. Chief Human Resource Officers (CHROs) have a potentially important role in defining and promoting appropriate human resource practices through human resource disclosures in corporate annual reports. We empirically examine the effect of CHROs on expanded human capital resource (HCR) disclosures, recently mandated by the SEC. We find that CHROs have a greater effect on the quality of HCR disclosures when they belong to the top management team, and less so when they belong to groups that are more poorly represented in top management, such as women, racial or ethnic minorities, or non-US nationals, and CHROs holding a liberal arts degree. Jointly considering the characteristics of CHROs, CEOs, and CFOs, we additionally find that pro-democratic political ideology is related to higher quality HCR disclosures. This study contributes to the literature by introducing a generalizable measure of HCR disclosure quality, uncovering significant heterogeneity in HCR disclosure quality across large US firms, and highlighting the role of CHROs in this process. In doing so, this study documents evidence that individual top executives in addition to the CEO and CFO can have a measurable effect on voluntary financial disclosures.
Keywords: CHROs; CEOs; CFOs; Human Capital Reporting